2012
DOI: 10.3148/73.1.2012.45
|View full text |Cite
|
Sign up to set email alerts
|

Body Fat, Sweetness Sensitivity, and Preference: Determining the Relationship

Abstract: Body fat measures were as effective as BMI measures in determining sweetness preference. Future research should be conducted to determine whether body fat and measures, such as waist circumference, can be predictive tools for sweetness preference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 11 publications
3
16
0
Order By: Relevance
“…The analysis of the relationship between the fat taste (character) preferences and the parents' body weight disturbances also shows no significant correlations, although some literature sources have suggested it [38]. Similarly to the study by Ettinger et al [39], a mother's sweet taste preferences were related to overweight and obesity, and in a particularly pronounced way with obesity. This result is in line with the observations of Matsushita et al [40], who conducted tests on over 29,000 people and found that sweet taste preferences are positively correlated with overweight and/or obesity of women and men.…”
Section: Discussionmentioning
confidence: 80%
“…The analysis of the relationship between the fat taste (character) preferences and the parents' body weight disturbances also shows no significant correlations, although some literature sources have suggested it [38]. Similarly to the study by Ettinger et al [39], a mother's sweet taste preferences were related to overweight and obesity, and in a particularly pronounced way with obesity. This result is in line with the observations of Matsushita et al [40], who conducted tests on over 29,000 people and found that sweet taste preferences are positively correlated with overweight and/or obesity of women and men.…”
Section: Discussionmentioning
confidence: 80%
“…Most studies did not show an association between body weight status and sweetness preference [71][72][73][76][77][78][79][80]. In one study, a significantly lower preference for sweetness among obese women compared to their normal weight counterparts was reported [74].…”
Section: Discussionmentioning
confidence: 99%
“…In 11 studies-eight in adults and three in children-associations between body weight and sweetness preference were assessed (Table S3-5 of Supplementary File S3). Of the eight studies conducted in adults, four were conducted solely in females [71][72][73][74], and in three of these studies, there were no significant differences between normal weight and overweight/obese females in their sweetness preference [71][72][73]. However, Connolly et al [74] found that obese women had a significantly lower preference for Ocean Spray Cranberry juice sweetened either with Truvia or sucrose compared to normal weight women.…”
Section: Body Weight and Sweetness Preferencementioning
confidence: 99%
“…None of the 34 variants examined were found to affect sweet taste. However, the study did not account for body mass index (BMI), which may affect sweet taste perception [14]. Further, the taste phenotyping method utilized relied on an individual's ability to recognize differences between sucrose solutions rather than quantifying more traditional measures of taste like detection thresholds and suprathreshold sensitivity.…”
Section: Introductionmentioning
confidence: 99%